2018
DOI: 10.1016/j.seizure.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of VNS therapy with AspireSR® (including cardiac-based seizure detection) at a large complex epilepsy and surgery centre

Abstract: The results suggest that approximately 70% of patients with existing VNS insertions could have significant additional benefit from cardiac based seizure detection and closed loop stimulation from the AspireSR device. For new insertions, the AspireSR device has efficacy in 59% of patients. The 'rule of thirds' used in counseling patients may need to be modified accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 19 publications
2
48
0
1
Order By: Relevance
“…In contrast, RNS is closed-loop, meaning that stimulation is delivered only when certain conditions are detected by the device [9]. More recent models of VNS have a sensing component, by which stimulation is provided when tachycardia is present [10].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, RNS is closed-loop, meaning that stimulation is delivered only when certain conditions are detected by the device [9]. More recent models of VNS have a sensing component, by which stimulation is provided when tachycardia is present [10].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy percent of patients could have significant additional seizure reduction with the Model 106. 37) Another study also revealed that VNS with AutoStim Mode achieved maintenance of prior-established seizure control with markedly less energy consumption and improved seizure control as compared to the previous models. 38) Patients who did not respond to the previous models only with the open-loop system may obtain seizure reduction by replacement to the Model 106 even though output currents and duty cycles were reduced.…”
Section: Implantable Devices For Medically Refractory Epilepsymentioning
confidence: 93%
“…The study involved patients under the care of one surgeon who had received new insertions of the model (51 patients) and those that had old VNS models that were updated at battery change (62 patients). The new (59% at a median of 13 months after insertion) and changed model patients both had better than expected responder rates over the period including a high rate of patients experiencing an additional seizure reduction in the changed model patients (71% had > 50% reduction in seizures following battery change) [106].…”
Section: Closed Loop Neurostimulationmentioning
confidence: 99%